Polyfunctionality of the English quantitative words - SHVACHKO, SVITLANA (Journal of Education Culture and Society, 2020)
The article in question considers the functioning of quantitative units, their language and speech aspects. Introduction focuses upon the major items of paper – definition of numerals, words of weight and measure, aims, methods of investigation, empiric mate-rial applied, evolution modifications, and perspectives of further study.